Democratization of terrorism: an analysis of vehicle-based terrorist events - Ryan Scott Houser (Trauma Surgery & Acute Care Open)
Objectives The COVID-19 pandemic inspired social changes that promote outdoor activities including eating at restaurants, which may linger in a world hyperfocused on disease transmission prevention, increasing the vulnerabilities to vehicle-based terrorism. Vehicle ramming attacks started to transition from a relatively rare method of attack to one of the most lethal forms of terrorism in Western countries just prior to the emergence of SARS-CoV-2. This study aims to provide a historical analysis of the terrorism-based attacks using vehicles between 1970 and 2019.Methods This study uses the methodology suggested by Tin et al in which the Global Terrorism Database hosted by the National Consortium for the Study of Terrorism and Responses to Terrorism was searched retrospectively for data. Data was collected from the database using the internal search function for terror events between January 1, 1970 and December 31, 2019 which used a vehicle as a means of attack.Results There were 257 recorded terror attacks that involved some type of vehicle between 1970 and 2019. The attacks resulted in 808 fatalities and 1715 injuries when excluding the September 11 attacks. 76 events occurred at the West Bank and Gaza Strip, 25 in the USA, 16 in Israel, and 14 in the UK. Of the 257 terror incidents, 71% (183) occurred within the last 6-year span of inquiry.Conclusion By 2016, vehicle attacks were the most lethal form of attack comprising just over half of all terrorism-related deaths in that year. Large gatherings such as festivals, sporting events, and now outdoor seating at restaurants, leave a number of people highly vulnerable to a vehicle ramming attacks depending on established countermeasures. The increased prevalence of outdoor activities and gatherings in a post-COVID-19 world will further expose large numbers of people to the potential vulnerabilities of vehicle-based terrorism. The scale of the casualties from a vehicle-based terror attack can overwhelm traditional resources and strain the abilities of the healthcare sector. Counterterrorism and disaster medicine specialists are crucial players in educating first responders and emergency medicine providers, allowing them to adequately prepare for an evolving threat in a world devastated by COVID-19.Level of evidence VI.